(untitled) (GAIMS Journal of Medical Sciences, 2025)
Background: Immunization is one of the most effective public health interventions, yet children of migrant construction workers often remain under-immunized due to unique socio-demographic and logistical barriers. This study aimed to evaluate complete immunization coverage and examine the effect of migratory factors on immunization among children residing at construction sites in Rajkot city, Gujarat. Material and methods: A cross-sectional study was conducted in 2019 in the field practice area of a community medicine department under Rajkot Municipal Corporation. A total of 244 children residing at construction sites were surveyed using a semi-structured questionnaire. Data on sociodemographic, immunization status, and migration history were collected and analyzed using appropriate statistical tests. Results: Full immunization coverage among the study population was 39.75%, while complete immunization coverage was 30.33%. Zero-dose prevalence was 12.7%. A statistically significant association was observed between immunization coverage and factors such as gender (p=0.00), birth order (p=0.00), and number of migrations (p=0.00), while place of migration showed no significant effect (p=0.23). The most common barriers to immunization were parental unawareness about vaccination sites (33.20%) and schedules (23.77%), followed by fear of wage loss due to post-vaccination illness (19.67%). Conclusions: Children of migrant construction workers in Rajkot city have considerably lower immunization coverage compared to district and national averages. Strengthening mobile outreach, increasing parental awareness, flexible session timings, and introducing incentives to offset wage loss could significantly improve immunization uptake among this vulnerable population.